2017
DOI: 10.1007/s00216-017-0561-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 89 drugs and other micropollutants in unfiltered wastewater and freshwater by LC-MS/MS: an alternative sample preparation approach

Abstract: A liquid chromatography-triple quadrupole-tandem mass spectrometry (LC-qQq-MS/MS) method was developed for simultaneous determination of 89 legal neuropsychiatric pharmaceuticals and illicit drugs (both parent compounds and metabolites) and other micropollutants in unfiltered wastewater and freshwater. The target chemicals fall under the classes of amphetamine-type stimulants, cocaine compounds, opiates and opioids, benzodiazepines, lysergic compounds, antipsychotics, anesthetics, antiepileptics, antidepressan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 24 publications
2
8
0
3
Order By: Relevance
“…In this sense, some compounds like caffeine and nicotine and their respective metabolites paraxanthine and cotinine, and some broadly used drugs like naproxen or acetaminophen are usually detected at higher concentrations (in the range of µg•L −1 ) than other pharmaceuticals. Other common pharmaceuticals like diclofenac, erythromycin or carbamazepine are usually in the range of ng•L −1 as previous research has indicated [10][11][12]. However, many studies evaluate the occurrence of pharmaceuticals during a short period of time; few studies examine these compounds in the long term to evaluate seasonal fluctuations and determine patterns from the presence of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, some compounds like caffeine and nicotine and their respective metabolites paraxanthine and cotinine, and some broadly used drugs like naproxen or acetaminophen are usually detected at higher concentrations (in the range of µg•L −1 ) than other pharmaceuticals. Other common pharmaceuticals like diclofenac, erythromycin or carbamazepine are usually in the range of ng•L −1 as previous research has indicated [10][11][12]. However, many studies evaluate the occurrence of pharmaceuticals during a short period of time; few studies examine these compounds in the long term to evaluate seasonal fluctuations and determine patterns from the presence of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, mass spectrometry has become an important tool in many fields such as pharmaceutics and life science, because of the characteristic of rapidity, sensitivity, and feasibility . As a soft ionization MS, electrospray ionization coupled with quadrupole extractive orbitrap MS (ESI‐QE‐Orbitrap‐MS/MS) could provide the accurate mass data for precursor and fragment ions.…”
Section: Introductionmentioning
confidence: 99%
“…İnsan vücudu dışında yapılan çalışmalar da ise şehirlerin atık sularında bulunan antidepresanların LC-MS/MS ile eş zamanlı tayini yapılmış ve 38 psikoaktif ilacın (benzodiazepinler, antidepresanlar ve istismar ilaçları dahil) ortalama ve maksimum konsantrasyon seviyelerinin literatürde daha önce rapor edilen seviyelerin üzerinde çıktığı bulunmuştur. 2017 yılında Sıvı Kromatografi-Üçlü Dört Kutuplu Tandem Kütle Spektrometresi (LC-MS/MS) yöntemi ile 89 yasal nöropsikiyatrik ilaç ve yasadışı uyuşturucunun (hem ana bileşikler hem de metabolitler) filtre edilmemiş atık su ve tatlı suda eş zamanlı belirlenmesi için metot geliştirilmiştir [12][13][14].…”
Section: Abstract: Depression Epilepsy Drug Antidepressant Antiepunclassified